Rejection of micropollutants by membrane filtration - Ozaki, Hiroaki (2004)
There is currently great interest in the removal of hazardous micropollutants to concentrations in the lower level than microgram per litter. For example, endocrine disrupting chemicals (EDCs) are exogenous substances which interfere with the normal function of hormones at very low concentration in human body. Many people and animals have been contaminated with EDCs taken in through water and food. Membrane technology is to be expected for one of the best way to concentrate the micro-pollutants in water and wastewater prior to the degradation of them. The effort to reduce the cost of energy required for reverse osmosis (RO) operation have led to the development of low pressure reverse osmosis (LPRO) membranes, categorically nanofiltration, for operation under very low pressure (below 0.5 MPa). Furthermore, the ultra-low pressure reverse osmosis (ULPRO) membranes, which are a new type of nanofiltration membrane, have received attention especially for their application in the field of water purification and wastewater treatment. Nanofiltration and ULPRO remove not only inorganic pollutants but also organics under lower pressure. In addition, the application of those membrane technologies to water and wastewater has widened their potentials to reject micro-pollutants in dissolved form such chemicals as endocrine disrupting chemicals (EDCs). In this study, we found that six types of EDCs: Bisphenol A (BPA), 17Î²-estradiol (E2), Nonylphenol (NP), Diethylphthalate (DEP), 2,4-Dichlorophenol (2,4-DCP), and Pentachlorephenol (PCP) could be rejected very effectively by the ULPRO membrane. Although the rejection of EDCs by using a relatively loose membrane (LPRO) showed lower values in a single solution system, the E2 rejection in mixture system of humic acid and E2 was almost 100%. In addition, it was found that the rejection properties of EDCs by LPRO membranes were affected by coexisting substances in water or wastewater. This paper also presents the data on the membrane rejection performance of dioxins, the most hazardous substance of EDCs, in the liquid of river sediment.